Change from Above, Language Contact, and Individual Change in Ælfric’s Linguistic Terminology - Yakovenko, Yekaterina (Studia Anglica Posnaniensia, 2019)
The paper combines a traditional semantic, morphological, and functional description of Ælfric’s terminology and its consideration within the frame of sociolinguistics; the analysis is supplemented by a cross-linguistic study of Ælfric’s terms with remarks on other Germanic languages. The results achieved enable us to argue that Ælfric’s linguistic terminology, being innovative, displays some features of change from above, arising from language contact and individual change.